(untitled) (African Journal of Biomedical Research, 2021)
Sickle Cell Disease (SCD) is prevalent in Nigeria with 150,000 new cases yearly, owing to poor knowledge, poverty and lack of screening. This study investigated knowledge and willingness to undergo genotype screening among young people who might be contemplating marriage or reproduction during or soon after the National Youth Service Corps (NYSC); the compulsory one year service for all Nigerian graduates from tertiary institutions. The study was a descriptive cross-sectional design, carried out amongst 355 respondents using a stratified random sampling. Both qualitative and quantitative methods were employed with due ethical considerations and analysis. The age range was between 18 and 30 years, with more female (54.6%) respondents. Almost all (96.3%) of the respondents have heard about SCD. The prevalence of SCD in the families of the respondents was 10.1% and majority (87.0%) have had genotype screening. Many (60.6%) had good knowledge about SCD but less than half (44.5%) could state the difference between genotype and blood group. Statistical associations were recorded between level of knowledge and gender, discipline of study and willingness. Concerted efforts should be geared towards SCD health education and screening using the platform of corps members’ during their orientation and weekly community development programmes.